Adopting Garfield (Raton, NM Raton Range, 1984)
Article is about the addition of Garfield to new toyland characters leading to the City of Bethlehem.
Newspaper article + photograph of Tom and Patti Jacks, Fred and Virgina Mack, Don and Donna Martin and James Cook
Master list item #: 15
File location is in the Raton file Cabinet
Keywords: Jacks, Tom; Jacks, Patti; Mack, Fred; Mack, Virginia; Martin, Don; Martin, Donna; Cook, James; Raton Lions Club; Grafield Chararacter; Toyland Display; Christmas Display; Display Additions; City of Bethlehem; Apache Avenue; Raton, New Mexico